(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
The judicial review of the decisions adopted by the health authorities with the aim of fighting against the COVID-19 pandemic are of notable importance from the point of view of the protection of the fundamental rights of citizens and respect for the nuclear principles of the State of Law such as the separation of powers. The legality and proportionality test that the courts are obliged to carry out is a guarantee against authoritarian temptations. Perhaps that is why, in order to save these jurisdictional controls, it has been chosen to apply constitutional exception tools that undermine the fundamental rights of citizens with much more weakened judicial control. Is it understood what this game is about?